STUDY OF NUMBER OF EPILEPSY CASES IN CITY SCHOOL STUDENTS OF THE SOUTH AREA OF MANAUS (Fiep Bulletin - online, 2014)
Epilepsy is usually known as a condition that made up of "a group of diseases that have in common seizures that happen without any fever, metabolic or toxic desease", and these seizures are caused by an abnormal and excessive discharge in the brain cells, the seizures can happen in a part of the brain (focal seizures) or in both hemispheres of the brain (general seizure) (Guerreiro, 1996, pg 01). This study had two phases, 1st Phase: Diagnose the positive cases applying the form of Placencia et al (adapted to schools) to teachers in the classrooms. Two situations were considered: positive test - to the forms that presented at least one affirmative answer, and the negative tests - when all the answers were negative. In the second phase the objective was to validate the diagnosis, through a neurologic consult to determine the true and false positives and negatives. In this research 65 suspects were detected, equivalent to 4,65% of the total of all students (1412), inferred that the rate of true positives would be inferior  to the suspects rate, that is according to literature, as an example Borges (2002) where, values between 0,9/1000 hab. to 57/1000 to the number of cases. Other authors that accept a smaller number of cases, between 1 to 10/1,000 hab. The quest for the number of cases of epilepsy in students was motivated by the attempt of setting a light on the pedagogical part of the prejudice problem. We tried to put an end to the myth of epilepsy and the prejudice that the people who have this disease have to face in a dayly basis.
Keywords: Epilepsy; Education